THE "TEA CUP EFFECT" AND REMOVAL OF SUSPENDED SOLIDS FROM WATER - MASHAURI, D A (Tanzania Journal of Engineering and Technology, 2017)
Suspended solids problem in water is an issue as old as water treatment itself. Suspended solids can be causative to eroding through abrasion of impellers, pump casings, pipes and other water works related appurtenances. It is therefore appropriate that suspended solids must be removed as early as possible in the water works treatment facilities. It is usually done at the river/lake intakes to reduce the coarse particulate matter that would otherwise adversely affect the water works thereafter. The fine particles that will escape the entrapment at the intake works would therefore require further and more effective system that would remove this fraction. By and large this removal process is achieved by chemically aided process such as coagulation/flocculation unit operation. This process is expensive and demands high level trained personnel to man them. In the same vein then a simple and effective system is proposed. This is a swirl or grit removal system that does not need any chemicals, moving parts or even highly trained personnel to operate them. This paper is looking at the theory of the "Tea Cup Effect" and how it has been used in practice to remove or reduce suspended solids from water. The paper gives some examples where such devices have been used and how effective they have been.